INFLUENCING OF PROJECT-BASED LEARNING MODEL TOWARD SCIENCE PROCESS SKILLS ON ENVIRONMENT MANAGEMENT MATERIAL - Sulton Nawawi; Amilda Amilda; Maya Puspita Sari (JURNAL PENA SAINS, 2017)
This study aims to determine the effect of the application of Project Based Learning Model to Skill of Science Process on Environmental Management Material. This research design uses posttest-only control design with Quasi-Experimental method (quasi-experiment). The sample of this research is 35 students. Based on the results of the analysis of students' science process skills show that the implementation of learning using the model of Project Based Learning is better than the conventional learning model. This can be seen from the calculation of the test-t skills of the science process shows for sig tcount 0.000 0,05, then Ha accepted and H0 rejected. The result of analysis of the average score of mastery of experimental science process skill class achieves 2.87 with good criteria while the students 'science process skill in control class 1.73 is sufficient to mean that the students' experimental class science process skill is higher than the control class science process skill. Thus, it can be concluded that the model of Project Based Learning affects the Skills of Science Process on Environmental Management Material.Keywords: project based learning model; skills of science process.